Career transitions in sport: bridging holistic developmental and ecological approaches - Stambulova, N.; Henriksen, K. (Psychology of Sport and Exercise, 2025)
The key idea of this review paper is to consider career transition scholarship in sport psychology through a lens of bridging holistic developmental and ecological approaches to demonstrate their intersections and complementarity in advancing the understanding of career transitions in sport. This paper is intended to: (a) outline an evolution of the career transition topic in sport psychology, emphasizing its development over the last 25 years; (b) summarize major current achievements of career transition research in bridging holistic developmental and ecological approaches; (c) address debates in, and formulate future challenges for, transition research and practice. We consider the evolution of the topic by analyzing the contributions of several milestone publications in Psychology of Sport and Exercise that prepared and spurred on the development of the bridges between transition research focusing on individual athletes and on their related environments. We proceed with situating career transition research within athlete career sport psychology discourse and propose a taxonomy of frameworks used in transition scholarship. Narrative synthesis underlined by bridging the two approaches in focus was used to summarize research- and practice-related knowledge on the transitions of athletes, coaches, and parents. In the final parts we invite the readers to debate some conceptual and research-to-practice issues within the topic as well as discuss future challenges in bridging the holistic developmental and ecological approaches in career transition research and practice.